RANCANG BANGUN APLIKASI SISTEM PERPAJAKAN DESA KARANG BINDU BERBASIS WEB - Rana Naftaly; Muchlis Muchlis; Sebri Hesinto (LPPM Universitas Putera Batam, 2023)
Karang Bindu Village is located in Rambang Kapak Tengah Prabumulih sub-district, South Sumatra. Led by the village head Mr. Iin Saputra. The administrator of Karang Bindu village has difficulties in collecting tax data, such as recording taxpayer data and proof of tax payments which are still being made manually. Therefore, it is hoped that there will be an application that can help admins in the tax data collection process. To obtain clearer information the author conducted research using qualitative descriptive methods. Where in this research the author used two data sources, namely, primary data and secondary data. In addition, data collection techniques were obtained from interview scripts and direct observation of the object of research and by looking for references through books or journals. After conducting this research, the authors collected the data obtained and then the authors resolved the existing problems by producing a